RANCANG BANGUN ASAP CAIR DARI TONGKOL JAGUNG MENGGUNAKAN PROSES PYROLYSIS - Sansaka, Fajar Hary; Abrina Anggraini, Sinar Perbawani; Iskandar, Taufik (eUREKA : Jurnal Penelitian Mahasiswa Teknik Sipil dan Teknik Kimia, 2017)
Liquid smoke obtained by burning dry biomass with high temperatures and little air (pyrolysis). Liquid smoke from corn cobs able to turn waste into food preservatives plantation substitute hazardous chemicals namely formaldehyde. fuel conversion efficiency is quite good, the energy density (energy content per unit volume) is quite high, and the ease of storage and distribution. Liquid smoke is used as a substitute for eating preservative chemicals or formaldehyde with a simple and inexpensive technology. Smoke-making process begins with the drying process, the enumeration process, the pyrolysis process and the process of purification, then after the final purification of smoke packed and marketed. Design of liquid smoke is expected to be in production with: 100 tons / year, while operating 300 days / year, 24 hours per day, divided into 3 shifts. Industrial locations will be built in the village Dadaprejo, District Junrejo, Batu, East Java. Form of industry is a Limited Liability Company (PT). Judging from the calculation of economic analysis to the design of liquid smoke, the obtained data is as follows: Total Capital Investment (TCI): Rp 2,171,285,991.14; Return Of Investment (ROIat): 34.06%; Play Out Time (POT) : 2.33 years. Break Even Point (BEP): 32.34%.; Shut Down Point (SDP): 4.83 tons / year; Internal Rate Of Return (IRR): 33.77%. It can be concluded that the design and construction of liquid smoke corn cob with fast pyrolysis process capacity of 100 tons / year worth to set up. Keywords: corn cobs, liquid smoke, and fast pyrolisis ABSTRAK Asap cair diperoleh dengan membakar biomassa kering dengan suhu tinggi dan sedikit udara (pirolisis). Asap cair dari tongkol jagung mampu mengubah limbah perkebunan menjadi pengawet makanan penganti bahan kimia berbahaya yaitu formalin. bahan bakar dengan efisiensi konversi cukup baik, densitas energi (kandungan energi per satuan volume) cukup tinggi, serta kemudahan dalam hal penyimpanan dan pendistribusian. Asap cair ini digunakan sebagai bahan pengawet makan penganti bahan kimia atau formalin dengan teknologi yang sederhana dan murah. Proses pembuatan asap diawali dengan proses pengeringan, proses pencacahan , proses pirolisis dan proses pemurnian, kemudian setelah pemurnian asap dikemas dan terakhir dipasarkan. Rancang bangun asap cair ini diharapkan dapat berproduksi dengan: 100 ton/tahun, waktu operasi 300 hari/tahun, 24 jam per hari , terbagi menjadi 3 shift. Lokasi Industri akan dibangun di Desa Dadaprejo, Kecamatan Junrejo, Kota Batu, Jawa Timur. Bentuk industri adalah Perseroan Terbatas (P T). Ditinjau dari perhitungan analisa ekonomi terhadap rancang bangun asap cair ini, maka diperoleh data sebagai berikut: Total Capital Invesment (TCI): Rp 2.171.285.991,14 ; Return Of Invesment (ROIat): 34,06 %; Play Out Time (POT): 2,33 tahun. Break Even Point (BEP): 32,34 %.; Shut Down Point (SDP): 4,83 ton/tahun; Internal Rate Of Return (IRR): 33,77%. Maka dapat disimpulkan bahwa rancang bangun asap cair dari tongkol jagung dengan proses fast pyrolysis kapasitas 100 ton/tahun layak untuk didirikan. Kata kunci: tongkol jagung, asap cair , dan fast pyrolisis